A 26-week repeated-dose toxicity study of allisartan isoproxil in Sprague-Dawley rats. (27th March 2013) - Liu, Yongzhen; Wang, Hao; Cheng, Yumei; Sun, Jingjun; Qiao, Junwen; Lu, Henglei; Zhu, Liang; Gong, Likun; Ren, Jin
Abstract: Allisartan isoproxil (ALS-3) is a selective, nonpeptide blocker of the angiotensin II type 1 receptor. It is a new antihypertensive drug under development with a novel chemical structure. The aim of this study was to evaluate the potential toxicity of ALS-3 in Sprague-Dawley rats. Animals were orally administered either vehicle or ALS-3 at doses of 20, 80 and 320 mg/kg once-daily for 26 weeks, followed by a 6-week recovery period. Toxicity was assessed by mortality, clinical signs, body weight, food consumption, hematology, coagulation, serum chemistry, gross necropsy, organ weights and microscopic examination. Decreased body-weight gain was noted at 320 mg/kg/day in both sexes as well as at the 80-mg/kg/day dose in females. Food consumption was decreased at all doses in males and at 80- and 320-mg/kg/day doses in females. Decreased erythrocyte parameters (erythrocyte count, hemoglobin and hematocrit) were observed in males receiving 320 mg/kg/day. Elevated urea nitrogen (BUN), increased kidney weight, decreased heart weight and exacerbation of chronic progressive nephropathy (CPN) severity were all observed in males at 80 and 320 mg/kg/day. However, only an exacerbated incidence of CPN was observed in females at 320 mg/kg/day. All changes were reversed after the 6-week recovery period, except BUN and CPN. Based on these results, we concluded that a dose of 20 mg/kg/day was the no observed adverse effect level. The toxicity target organ was the kidney. Males were more affected than females.